Correlation between Alpha Fetoprotein (AFP) Levels and Characteristics of Liver Lesions Using Computed Tomography (CT) scan in Hepatocellular Carcinoma: a Study at Dr. Hasan Sadikin Central General Hospital Bandung 2019 - Ristaniah D. Soetikno*, Iin Hatta, Leni Santiana, Dian Komala Dewi (Innovative Journal of Medical and Health Sciences, 2020)
Introduction: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver which is about 75% - 85%. The diagnosis of HCC is determined based on several factors, including the background of chronic liver disease, tumor markers, and imaging diagnosis. There are three main growth patterns of HCC that can be seen on computed tomography (CT) scan : massive, nodular, and diffuse infiltrative. HCC is locally invasive and tends to invade the portal vein, inferior vena cava and bile duct. Alpha fetoprotein (AFP) is one of the tumor markers used for early diagnosis of KSH and plays an important role in the development and progression of HCC. Objective : To determine the correlation between alpha fetoprotein levels with characteristics of liver lesions using CT scan examination in HCC patients. Methods : This study was an observational analytic study with a cross-sectional design. Sampling was done retrospectively by collecting medical record data and the results of abdominal CT scan readings from January to December 2019. The study was conducted at the Department of Radiology, Department of Clinical Pathology and Installation of Medical Records-SIRS Hospital Dr. Hasan Sadikin Bandung in February - April 2020. Univariable analysis was carried out to see the description of the proportion of each variable to be presented descriptively, which could be explained into descriptive analysis and hypothesis testing. Results : There were 63 subjects, 48 men (76.2%), 15 women (23.8%), with the youngest age of 21 years, the oldest 86 years with an average age of 53.44 years. The highest average AFP levels were found in the group of patients with diffuse infiltrative growth patterns 93064.84 ± 177486,301 and the presence of a thrombus in the portal vein of 78770.98 ± 88358,791. The results of statistical tests using the Mann Whitney Test showed that there were significant differences between the levels of AFP and the growth pattern of liver lesions in HCC patients based on the results of the CT scan with a value of p = 0.040 (p?0.05) and there were significant differences between the levels of AFP and portal vein thrombus in HCC patients based on the results of CT scan examination with a value of p = 0.040 (p?0.05). Conclusion : There is a significant correlation between AFP levels with the characteristics of liver lesions specifically the form of growth patterns and the presence of portal venous thrombus using CT scan examination of HCC patients in dr. Hasan Sadikin General Hospital. Keywords : Hepatocellular carcinoma, Alpha fetoprotein, CT scan